2004
DOI: 10.5194/acp-4-147-2004
|View full text |Cite
|
Sign up to set email alerts
|

Halogen cycling and aerosol pH in the Hawaiian marine boundary layer

Abstract: Abstract. Halogen species (HCl * (primarily HCl), Cl * (including Cl 2 and HOCl), BrO, total gaseous inorganic Br and size-resolved particulate Cl − and Br − ) and related chemical and physical parameters were measured in surface air at Oahu, Hawaii during September 1999. Aerosol pH as a function of particle size was inferred from phase partitioning and thermodynamic properties of HCl. Mixing ratios of halogen compounds and aerosol pHs were simulated with a new version of the photochemical box model MOCCA that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 64 publications
2
85
1
Order By: Relevance
“…R1 was characterized by high concentrations of sea salt particles with the average molar ratio of chloride to sodium (Cl − / Na + ) close to unity. This is not necessarily expected in submicron aerosols in the tropical oceanic regions, because rapid acidification of sea salt particles occurs on the timescale of seconds (e.g., Pszenny et al, 2004;Keene et al, 2009). The fact that a depletion of Cl − is apparently less pronounced in R1 indicates that the concentrations of gas species including organic acids (e.g., Laskin et al, 2012) responsible for the Cl − loss were substantially low in R1.…”
Section: Characteristics Of Sea Salt Particlesmentioning
confidence: 99%
“…R1 was characterized by high concentrations of sea salt particles with the average molar ratio of chloride to sodium (Cl − / Na + ) close to unity. This is not necessarily expected in submicron aerosols in the tropical oceanic regions, because rapid acidification of sea salt particles occurs on the timescale of seconds (e.g., Pszenny et al, 2004;Keene et al, 2009). The fact that a depletion of Cl − is apparently less pronounced in R1 indicates that the concentrations of gas species including organic acids (e.g., Laskin et al, 2012) responsible for the Cl − loss were substantially low in R1.…”
Section: Characteristics Of Sea Salt Particlesmentioning
confidence: 99%
“…Pszenny et al (2004). Table 1 gives the 24-h model mean concentrations of oxidants for each data set.…”
Section: à3mentioning
confidence: 99%
“…The oxidation of S(IV) to S(VI) in liquid water, the primary pathway of sulfate formation, is highly sensitive to pH (Chameides, 1984). Halogen chemistry is strongly influenced by particle acidity, which has direct implications for the oxidation of volatile organic compounds (VOCs) and ozone formation in marine and coastal regions (e.g., Sander and Crutzen, 1996;Pszenny et al, 2004). Recent evidence has demonstrated that aerosol pH is also a critical parameter influencing halogen chemistry in continental locations (Brown et al, 2013;Thornton et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%